A Phenomenological Study on Issuess Of Planning and Budgeting Consistency in The Perspectives of Local Government Budget Team - Ocktavianto, Eko Prasetyo; Triyuwono, Iwan; Purwanti, Lilik (Universitas Negeri Malang, 2017)
This study aims to gain an understanding of the importance of maintaining the consistency of planning and budgeting from the viewpoint of the Local Government Budget Team (TAPD). Using a phenomenological approach allows the disclosure of meaning systematically related to the phenomenon being studied. The study was developed using primary and secondary data sources. The primary data were derived from unstructured interviews and the secondary data used by researcher were in the form planning and budgetting documents, namely, RPJMD, RKPD, KUA PPAS and APBD. Some findings indicate that there are still many problems in the process of budget planning and budgeting at the research site. The problems manifest in the form of constraints in achieving consistency in planning and budgeting caused by both internal and external factors. Eventually, the results of the study conclude that efforts to maintain the consistency of planning and budgeting interpreted by TAPD of Probolinggo as guidance in realizing the accountability of the financial performance of local government through loyalty, effective evaluation and supervision and strong commitmen from the employees.Â Keywords: budget, consistency, planning and budgeting, TAPD